2011
DOI: 10.1007/s10973-010-1257-z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and DSC study of mineral–carbon sorbents obtained from coal tar pitch–polymer compositions

Abstract: The purpose of this study was to determine the possibility of producing hydrophobic mesoporous mineralcarbon sorbents from aluminum hydroxide and compositions of coal tar pitch-polymers on carbonization at 600°C in a nitrogen atmosphere. Blends of the products of co-precipitation of aluminum hydroxide in the carbonaceous substances medium were subjected to carbonization process. The extent of porous structure development was evaluated using low temperature nitrogen adsorption, adsorption of benzene vapors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As a high-melting, rigid and spinnable duroplast, PAN is a very useful raw material for the preparation of microporous activated carbon and carbon fibers by controlled pyrolysis followed by an appropriate chemical and/or thermal activation [1][2][3][4]. PAN-derived activated carbons are applied as the adsorbents for the removal of heavy metal ions and organic pollutants from aqueous solutions as well as volatile organic compounds (VOCs) from exhaust gases [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As a high-melting, rigid and spinnable duroplast, PAN is a very useful raw material for the preparation of microporous activated carbon and carbon fibers by controlled pyrolysis followed by an appropriate chemical and/or thermal activation [1][2][3][4]. PAN-derived activated carbons are applied as the adsorbents for the removal of heavy metal ions and organic pollutants from aqueous solutions as well as volatile organic compounds (VOCs) from exhaust gases [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…They are aimed at the improvement of utility properties of coaloriginated bitumen and utilization of waste polymers [17][18][19][20]. It was demonstrated that pitch-polymer compositions can be used for the preparation of carbon adsorbents [21][22][23] and mineral-carbon adsorbents [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Modification of coal-tar pitch with unsaturated polyester resins leads to considerable plasticization, and such modified bitumens of significantly lower cancerogenicity can be used as binders with insulating and sealing properties. The coal-tar pitch with the addition of poly (ethylene terephthalate) or polycarbonate is characterized by increased thermal and mechanical resistance [10], and it can be used as a promotor of porous materials of great specific surface [11][12][13]. Thermal factor played a decisive role in all examinations.…”
Section: Introductionmentioning
confidence: 99%